An Appraisal of ECOWAS in the 2023 Military Intervention in Niger Republic’s Politics - Solaru, Oladapo Emmanuel Solaru; Amodu, Akeem Amodu (African Journal of Stability and Development (AJSD), 2025)
The Economic Community of West African States (ECOWAS) has consistently been instrumental in fostering regional stability; however, its suggested military intervention after the 2023 coup in Niger Republic sparked significant discussions regarding the legitimacy, efficacy, and political ramifications of such measures. This paper evaluates ECOWAS’s reaction to the July 2023 military coup that removed President Mohamed Bazoum, analysing the regional organisation’s transition from diplomatic measures to the consideration of military intervention. The primary issue examined is the seeming disjunction between ECOWAS’s normative pledges to democracy and the actual constraints in upholding constitutional order, particularly amid increasing public scepticism and regional security instability. The objective of the study is to critically examine the role played by ECOWAS in the 2023 military intervention in Niger Republic’s politics. The research is guided by the question: What role did ECOWAS play during the 2023 military intervention in Niger’s politics? The study employs a qualitative methodology, utilising content analysis of official ECOWAS communiqués, interviews with regional policy analysts, and secondary sources including academic literature and news media. Initial findings indicate that although ECOWAS aimed to prevent the proliferation of coups and reinforce its normative authority, the action divided member states and incited local opposition in Niger, highlighting issues of legitimacy and regional cohesion. The paper concludes that ECOWAS’ strategy to the Niger’s political crisis demonstrates a tenuous equilibrium between normative enforcement and geopolitical realities. The intervention threat revealed internal fissures within the bloc and underscored the necessity for more participatory and locally rooted dispute management procedures. This evaluation provides insights into the changing functions of regional organisations in Africa’s democratic consolidation and peacebuilding initiatives.